Best practices of the social innovations in the framework of the e-government evolution - Vasja Roblek; Mirjana Pejić Bach; Maja Mesko; Tine Bertoncel (Amfiteatru Economic Journal, 2020)
The social innovations have been together with the advanced technology in the 21st century, taking an essential role in social structures and their informatization processes. Information technology has become an indispensable factor not only in industry and service businesses, but also in governing systems at the micro (cities and regions) and macro (state and nations) levels. The information processes, which includes automation, have in the last few years an important impact on the transformation from "classical" governance into the "smart governance". In the paper are presented the best practices which show how could social innovations, together with the advanced technology also lead to the several democratic changes in the urban environment. It can be concluded that it will in many ways reorganize public decision - makings, create changes in democratic processes that are in accordance with socioeconomic and technological development, and will represent the basis for the emergence of the so-called the smartest social community and the ensuing novel processes of organization and operation.
Keywords: D71; D72; D73; O33; O35; 330; best practices; e-government; e-participation; governance; public value theory; smart governance; social innovations